Strong genetic subdivision generates high genetic variability among eastern and western Australian populations of Lutjanus carponotatus (Richardson) - Veilleux, H.; van Herwerden, L.; Evans, R.; Travers, M.; Newman, Stephen (Elsevier BV, 2011)
Lutjanus carponotatus ranges from the Indian Ocean to northern Australia and Papua New Guinea and is an important species for both commercial and recreational fisheries. Due to its life history characteristics and fishing pressures, L. carponotatus is vulnerable to overfishing and suitable management is essential. This phylogenetic and population genetic study assessed the population genetic structure of L. carponotatus at seven locations in three bioregions in Western Australia (WA) using the mitochondrial DNA control region. Analysis of molecular variance (AMOVA) indicated no genetic differentiation among locations within (øCT=0.051) and among bioregions (øSC=-0.026). Phylogenetic analyses indicated no geographic partitioning within WA, though two distinct lineages were found. Within these two lineages there was no significant spatial partitioning, suggesting a panmictic population that can, under current conditions, be managed as a single stock. WA and Great Barrier Reef (GBR) population genetic data were then combined to determine the broad-scale connectivity between the east and west coast of Australia. L. carponotatus from the GBR did differ significantly (FST=0.64, p=<0.001) from the WA population, indicating the two populations do not exchange any migrants and should be managed as discrete stocks. As an indicator of population resilience, genetic variability was compared among WA and GBR populations of L. carponotatus and we show that the WA population has almost three times the genetic variability of the GBR population, suggesting that it will be better able to adapt to environmental change expected during the 21st century. © 2010 Elsevier B.V.